Conversion Eugenol to Vanillin: Evaluation of Antimicrobial Activity - Triana, Desita; Tafdila, Muhammad Akbar; Antika, Lucia Dwi; Ernawati, Teni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Indonesia is known as one of the largest clove producing countries in the world. About 75-90% main component of the clove oil is eugenol. Eugenol can be used as an analgesic, local anaesthetic, and also recognized as antimicrobial. Eugenol is known as starting material to produce synthetic vanillin. Vanillin is a compound that can be isolated from vanilla (Vanilla p lanifolia) or chemically synthesis. Vanillin is widely used for flavouring, fragrance, and also as a precursor of drugs in the pharmaceutical industry. Conversion eugenol to vanillin through several phases including isomerization, acetylation, oxidation, and hydrolysis. From each phase, it produces intermediate products, there are isoeugenol, isoeugenol acetate, and vanillin acetate, and also produce by-product vanillic acid. This present study aims to evaluate the results from the conversion of eugenol to vanillin for its antimicrobial activity against pathogenic bacteria E. coli and S. aureus. The result showed that eugenol, isoeugenol, vanillin acetate, vanillin and vanillic acid had antimicrobial activity. Isoeugenol which is the result of isomerization of eugenol is known to possess the best antimicrobial activity.